Metabolic syndrome, high-sensitivity C-reactive protein and the risk of heart failure: the Kailuan cohort study - Tian, Yan; Wang, Yanxiu; Zhao, Dandan; Sun, Huayu; Wu, Hao; Yang, Peng; Wu, Shouling; Wu, Ying; Chen, Shuohua; Li, Yun (Frontiers in Endocrinology, 2025)
BackgroundMetabolic syndrome (MetS) and elevated high-sensitivity C-reactive protein (hs-CRP) have been identified as risk factors for heart failure (HF) in some studies. However, little was known about the co-exposure of MetS and inflammation to HF. We aimed to investigate the combined effect of MetS and high hs-CRP levels on the risk of incident HF.MethodsThe study included 94,841 participants without HF selected from the Kailuan cohort in 2006 (the baseline) and then followed up until 31 December 2020. Participants were divided into four groups based on the presence of MetS and high hs-CRP levels (>3mg/L) at baseline: MetS-CRP- (n=53,937), MetS-CRP+ (n=10,338), MetS+CRP- (n=23,521), MetS+CRP+ (n=7,045). Cox regression models were used to analyze the association of MetS and inflammation with the risk of HF. Statistical significance was defined as a two-tailed P value < 0.05.ResultsThe mean age of the participants was 51.5 ± 12.5 years, and 75,976 (80.0%) were male. During 13.1 years of follow-up, 3,058 participants were diagnosed with HF. The HF incidence rate of four groups were 1.69/1000pys, 2.95/1000pys, 3.27/1000pys, 5.33/1000pys. The HR for MetS-CRP+, MetS+CRP-, and MetS+CRP+ were 1.29 (95% CI, 1.15-1.45), 1.40 (95% CI, 1.29-1.53), and 1.85 (95% CI, 1.65-2.06), respectively, compared with MetS-CRP-. After stratification by age (p for interaction < 0.01), compared with the MetS-CRP- group, the HR of the MetS+CRP+ group was 2.17 (95% CI, 1.83-2.57) in participants with < 60 years and 1.53 (95% CI, 1.32-1.78) in participants with ≥ 60 years. There was an interaction between groups and ues of antihypertension medication (p for interaction <0.01). Compared with MetS-CRP-, the risk of HF in the MetS+CRP+ group was increased 1.38-fold (95% CI, 1.12-1.70) in participants with antihypertension medication use and 2.00-fold (95% CI, 1.75-2.27) in participants without antihypertension medication use.ConclusionsThe combination of MetS and elevated hs-CRP was associated with increased risk of HF in the Chinese population.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR-TNRC-11001489.